Parallel self‐testing for device‐independent verifiable blind quantum computation. Issue 3 (26th August 2020) - Xu, Qingshan; Tan, Xiaoqing; Huang, Rui; Zeng, Xiaodan
Abstract: With advances in experimental quantum computing, the requirement for verifying the correctness of quantum computation is urgent. The recent protocols of device‐independent verifiable blind quantum computation provide a fruitful solution. However, all existing approaches have relatively high overhead. In this paper, we present a parallel self‐testing technology to extract the presence of tensor products of Pauli observables on maximally entangled state. We then utilize our parallel self‐testing to propose a device‐independent verification protocol. Finally, compared to other existing protocols, our scheme has a lower overhead, which costs O ( n 11 log n ) Bell pairs, where n is the size of original computation.